Development of the Japanese version of the Preschool Confusion Assessment Method for the ICU. Issue 1 (15th September 2017) - Matsuishi, Yujiro; Hoshino, Haruhiko; Shimojo, Nobutake; Enomoto, Yuki; Kido, Takahiro; Jesmin, Subrina; Sumitani, Masahiko; Inoue, Yoshiaki
Abstract : Aim: Delirium is associated with various negative clinical outcomes, such as decline in cognitive ability, increased length of hospital stay, and higher mortality. For these reasons, early diagnosis of delirium is critical. Unfortunately, there are no reliable diagnostic criteria or tool of delirium for infants and preschool‐aged children in Japan. The aim of the present study was to translate a new delirium assessment tool, the Preschool Confusion Assessment Method for the Intensive Care Unit (psCAM‐ICU), for accurately diagnosing clinically ill infants and preschool‐aged children, from English to Japanese. Methods: The translation was undertaken with the internationally established back‐translation method. The translation was repeated blindly and independently by eight medical researchers and clinicians from multiple disciplines. Any discrepancy evident from the translated works was discussed and resolved. Results: We report the successful development of the Japanese version of psCAM‐ICU. However, before its full application, this diagnostic tool requires further testing and study, most notably for its validation and reliability. Conclusion: A Japanese version of the psCAM‐ICU was developed. Abstract : A Japanese Version of The Preschool Confusion Assessment Method for the ICU(psCAM‐ICU) was developed